Identification of atypical ATRNL1 insertion to EML4-ALK fusion gene in NSCLC - Robesova, Blanka; Bajerova, Monika; Hausnerova, Jitka; Skrickova, Jana; Tomiskova, Marcela; Dvorakova, Dana (Lung cancer, 2015)
We herein present a rare case of an EML4-ALK positive patient. A 61-year-old man was diagnosed with locoregional non-small cell lung cancer (NSCLC). No EGFR mutations were detected, and therefore the ALK rearrangement was evaluated using immunohistochemistry (IHC), fluorescence in situ hybridization (FISH) and the reverse transcription PCR (RT-PCR) method for EML4-ALK. All methods showed a positive result and, therefore, the patient was treated with crizotinib with a good therapeutic response. However, a detailed RT-PCR analysis and sequencing revealed an unexpected 138 bp insertion of attractin-like 1 (ATRNL1) gene into the EML4-ALK fusion gene. In our case, the positive therapeutic response suggests that ATRNL1 insertion does not affect EML4-ALK's sensitivity to crizotinib. This case shows great EML4-ALK heterogeneity and also that basic detection methods (IHC, FISH) cannot fully specify ALK rearrangement but in many cases a full specification seems to be important for an effective TKI indication, and sequencing ALK variants might contribute to optimized patient selection.
Keywords: pyridiny; Base Sequence; Mutagenesis, Insertional; inhibitory proteinkinas; nemalobuněčný karcinom plic; výsledek terapie; nádory plic; fúzní onkogenní proteiny; Pyrazoles; lidé; pyrazoly; Molecular Sequence Data; staging nádorů; Oncogene Proteins, Fusion; Treatment Outcome; Radiography, Thoracic; inzerční mutageneze; molekulární sekvence - údaje; Male; Protein Kinase Inhibitors; Carcinoma, Non-Small-Cell Lung; Pyridines; sekvence nukleotidů; Sequence Analysis, DNA; rentgendiagnostika hrudníku; Lung Neoplasms; lidé středního věku; mužské pohlaví; sekvenční analýza DNA; Middle Aged; Neoplasm Staging; Humans